Eksistensi Komunikasi Orang Tua dalam Meminimalisir Speech Delay pada Anak Usia Dini (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
Parental communication plays an essential role in preventing speech delay among early childhood learners. This article examines the existence and significance of parent–child communication as a non-formal educational effort to minimize speech delay. The study employed a literature review method by analyzing books, scientific journals, and official reports from professional institutions such as the Indonesian Pediatric Society (IDAI). Findings indicate that insufficient verbal stimulation, limited parent–child interaction, and lack of responsive communication contribute significantly to delays in children's speech development. Warm, consistent, and affectionate communication has been proven to enhance children’s language skills, emotional security, and confidence. Furthermore, simple daily activities such as storytelling, dialogue, and joint play serve as effective forms of language stimulation. The study emphasizes that parent–child communication is not only a medium for exchanging information, but also an important foundation for fostering children’s linguistic, emotional, and social development. The implications of this study highlight the need for strengthening communication practices within families as a preventive strategy against speech delay and as a fundamental component in optimizing early childhood development.